THE RELEVANCE OF WAQF IN SUPPORTING ENVIRONMENTAL EDUCATION AND SUSTAINABLE DEVELOPMENT - Abubakar Muhammad, Adamu; Yakub, Abubakar Aliyu; Mikail, Usman Jibril; Ibrahim, Aliyu (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
Climate change and environmental degradation have become major worldwide issues, particularly in poorer nations. There are still gaps in funding and community-level instruction for sustainable environmental practices, despite global commitments to the Sustainable Development Goals (SDGs). Although the Islamic institution of waqf, a type of perpetual charity endowment, has long been important for social welfare, little is known about how it might help with sustainability and environmental education. The purpose of this study is to investigate the applicability and potential of waqf in advancing sustainable development and environmental education. It looks at how waqf can be set up and used to support environmental initiatives, ecological literacy, and awareness-raising initiatives both inside and outside of Muslim communities. Using content analysis of original Islamic law sources, historical case studies, and modern waqf models from nations like Malaysia, Indonesia, and Turkey, a qualitative research approach was used. To learn more about real-world applications and difficulties, semi-structured interviews were also done with community leaders, environmental academics, and waqf officials. By creating eco-friendly schools, assisting research facilities, financing green technology, and supporting awareness campaigns based on Islamic ecological ideals, waqf can make a substantial contribution to environmental education and sustainable development, according to the study. Examples from history show that waqf holdings were historically utilized to protect public amenities and natural resources like forests and water sources. In certain nations with a majority of Muslims, contemporary waqf organizations are already starting to adjust to sustainability goals. However, because of a lack of knowledge, legal restrictions, and a lack of creativity in waqf management, this integration is still quite low. The scope of this study focuses on a few Muslim-majority nations with operational waqf organizations. Access to waqf administrative documents and some parties' reluctance to reveal financial strategies are further barriers to empirical data